EKOFEMINISME TOKOH PEREMPUAN DALAM NOVEL CHEMISTRY CINTA DI WAKATOBI KARYA DEDI OEDJI - NFN Nursyamsi; NFN Faisal; NFN Sakaria (Kantor Bahasa Provinsi Gorontalo, 2020)
AbstractInjustice towards women in the environment concerns the exploitation by humans of nature. Conceptually, women's feminist issues have a relationship to ecological issues. The novel Chemistry Cinta di Wakatobi by Dedi Oedji tells the story of the Bajo fishing community of various ecological problems in Wakatobi. This study aims to examine the relationship between nature and women in the novel Chemistry Cinta di Wakatobi based on the perspective of Keren J Werren socialist ecofeminism theory. This research is a qualitative descriptive study. The research data comes from the novel Chemistry Cinta di Wakatobi. The research data were collected using reading and note-taking techniques. Furthermore, the collected data were analyzed based on studies of socialist ecofeminism. The results showed that the form of the relationship between nature and Wakatobi women is reflected in the figures of Anisa, Wa Dambe, and Wa Tanihi. Relationships that exist in the form of conservation or provision of protection of nature, utilization, and preservation of nature maintain food security and strengthen women's access to the use of natural resources.